Microstructure and transport properties of lithium hexafluorophosphate solutions in binary mixture of dimethyl carbonate with ethylene carbonate from molecular dynamics simulation - Dmytro Dudariev; Yevhenii Holubenko; Rebie Jallah; Oleg Kalugin (Вісник Харківського національного університету: Серія xімія)
Solutions of Li+ salts in many non-aqueous solvents used in Li-ion batteries have a maximum conductivity curve depending on the electrolyte concentration. For the microscopic interpretation of this phenomenon for one of the most popular electrolytes, LiPF6 solutions in a binary mixture of dimethyl carbonate (DMC) / ethylene carbonate (EC) (1:1), molecular dynamics simulations of the corresponding systems with a salt content of 0.1, 0.5, 1.0, 1.5 and 2.0 M were performed. The potential models for DMC and EC molecules were developed as the combination of two different force fields: OPLS-AA and GAFF in order to properly reproduce the diffusion coefficients of pure solvents. The structure has been analyzed in terms of radial distribution functions (RDFs) and running co-ordination numbers (RCNs). The results show that Li+ cation can form contact ion pairs (CIPs) and solvent shared ion pairs (SSIPs) in the solutions. The total coordination number of the cation remains the same at around 5.5-6.0 for all concentrations. Also, EC molecules and PF6- anions are competing for the position in the first coordination shell of the cation. The aggregate analysis with two different distance criteria was performed: minima on the RDFs and the minima on the second derivative of the RCNs. The diffusion coefficients for all components of the solutions and viscosity of simulated systems were also obtained. The diffusion coefficients for all components are decreasing and viscosity values are non-linearly increasing with the salt concentration increase. The conductivity values were obtained with the diffusion coefficient values of ions via Nernst-Einstein relation. These findings and the drastic viscosity increase at 1.0 M and at higher concentrations of LiPF6 are in agreement with the calculated experimental conductivity values.